2007
DOI: 10.1111/j.1572-0241.2007.01373.x
|View full text |Cite
|
Sign up to set email alerts
|

COX-2 CA-Haplotype Is a Risk Factor for the Development of Esophageal Adenocarcinoma

Abstract: The COX-2 CA-haplotype is more frequently observed in patients with EAC than in patients with BE and reflux esophagitis. These data suggest a direct link between COX-2 activity and neoplastic progression in patients with BE and reflux esophagitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 41 publications
3
24
1
3
Order By: Relevance
“…In addition, the COX-2 polymorphism data in our patients are very similar to the recently reported COX-2 -765 and -1195 genotype distributions in Dutch esophageal adenocarcinoma patients by Moons et al [17] , except for the -1195 GG genotype, which was present in 8.0% of our patients vs only 2.0% in the patients in the study by Moons et al [17] .…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…In addition, the COX-2 polymorphism data in our patients are very similar to the recently reported COX-2 -765 and -1195 genotype distributions in Dutch esophageal adenocarcinoma patients by Moons et al [17] , except for the -1195 GG genotype, which was present in 8.0% of our patients vs only 2.0% in the patients in the study by Moons et al [17] .…”
Section: Discussionsupporting
confidence: 72%
“…Analyzing the COX-2 haplotypes showed that the GG/GG haplotype was present more often in the esophageal carcinoma group, which again is not in accordance with the results of Zhang et al [12] and Moons et al [17] , who both found that the CA containing haplotypes carried the highest risk. Since the results of Zhang et al [12] and Moons et al [17] on different types of tumors (squamous cell carcinoma vs adenocarcinoma, respectively) are very similar, and more or less contradict our results, it was of interest to compare the haplotype distribution between our patients with squamous cell carcinoma vs adenocarcinoma.…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations